2006
DOI: 10.1143/jjap.45.l419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurity of MgO Substrates on Properties of Molecular Beam Epitaxy-Grown Superconducting NdBa2Cu3O7-δ Thin Films

Abstract: Classical mechanics has been applied in the theoretical study of the ionization of hydrogen atoms by static electric and circularly polarized electromagnetic fields. In both cases it was assumed that the ionizing field was adiabatically switched on. In the case of circular fields the calculations were performed for the initial energies E 0 = −1/2n 2 0 and frequencies of the field ω for which ωn 3 0 0.44. For such initial conditions almost all trajectories that lead to ionization are regular. The results of adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…High quality (001) MgO substrates with low Ca impurity levels of less than 250 ppm have been used to minimize contamination by segregated Ca. 8 The MgO substrates were annealed for 12 h in flowing oxygen at 1000 C prior to the introduction into the ultra-high vacuum (UHV) chamber. The growth temperature T growth was varied from 520 C to 720 C, which was monitored by an optical pyrometer.…”
Section: Methodsmentioning
confidence: 99%
“…High quality (001) MgO substrates with low Ca impurity levels of less than 250 ppm have been used to minimize contamination by segregated Ca. 8 The MgO substrates were annealed for 12 h in flowing oxygen at 1000 C prior to the introduction into the ultra-high vacuum (UHV) chamber. The growth temperature T growth was varied from 520 C to 720 C, which was monitored by an optical pyrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Deviations from perfect crystallinity in MgO can have detrimental effects on its functionality. It was shown that poor-quality MgO substrates gives rise to poor-quality thin films 70 , while defects and impurities can lead to a degradation of the superconducting properties in high-T c superconductors 72,75 . On the other hand it is known that doping Fe/MgO/Fe tunnel junctions with carbon impurities increases the output voltage and reduces noise 76,77 .…”
Section: B Magnetism In Doped Mgomentioning
confidence: 99%